Development of a transportable High-Performance Liquid Chromatograph with Ultraviolet detection and a method for the rapid analysis of 13 carbonyl compounds hydrazones - Audrey Grandjean; Anaïs Becker; Mathilde Mascles; Franck Amiet; Jean-Philippe Amiet; Damien Bazin; Stéphane Le Calvé (Journal of Chromatography Open)
In environments with elevated air pollution, highly reactive aldehydes pose significant health concerns. This study proposes a simultaneous analysis of 13 carbonyl compounds, according to the ISO 16,000–3 reference method, adapted for a novel transportable High-Performance Liquid Chromatograph (HPLC) system. The transportable HPLC system consists of a reinforced analytical suitcase and a computer suitcase, each equipped with spring systems to fortify them against impact. The system features a straightforward isocratic pump, ensuring reliability and ease of operation, while sample delivery is managed by a piston pump coupled to a multiplexing valve. Derived carbonyl compounds with 2,4-dinitrophenylhydrazine were separated in isocratic mode using water and acetonitrile with a reverse-phase column in less than 20 min. Out of the 13 hydrazones, only 2-butanone-2,4-DNPH (BO-DNPH) and butanal-2,4-DNPH (BA-DNPH) were fully coeluted, and separation of the other critical pairs containing 3 and 4 carbons was achieved. The method was applied to the transportable HPLC equipped with a UV or light-emitting diode (LED) detector. These results were compared with the ones obtained on two benchtop laboratory HPLCs equipped with a diode array detector (DAD). The limit of detection (LOD) for the hydrazones of the carbonyl compounds ranged from 0.12 to 0.38 mg L–1 with the UV detector and 0.45 to 1.04 mg L–1 with the LED detector. Precision was determined from consecutive injections of the analytes to yield RSD<11.5% (UV) and RSD<14.1% (LED). Performances were close to that of the laboratory HPLCs, either in sensitivity, resolution, or repeatability with overall more accurate and robust results with the UV than with the LED detector. Despite the LED system not fully meeting the standard method requirements with linearities correlation coefficients lower than 0.999, both systems and methods were validated for the isocratic analysis of hydrazones for aldehydes and ketones quantification. An additional comparison was made with the literature regarding both the isocratic method developed and the transportable system.